Antegrade Posterior Interosseous Flap for Nonhealing Wounds of the Elbow: Anatomical and Clinical Study. Issue 11 (November 2018) - Zaidenberg, Ezequiel Ernesto; Zancolli, Pablo; Farias Cisneros, Efrain; Miller, Aden Gunnar; Moreno, Rodrigo
Abstract : Background: The posterior interosseous artery (PIA) flap has been widely reported to cover defects at the dorsal aspect of the hand. However, the use of this flap to cover elbow defects has been rarely reported. The purpose of this study was to analyze the anatomical feasibility of the PIA flap to cover elbow soft-tissue defects and, additionally, to review the clinical outcomes of patients treated with this flap. Methods: An anatomical study was performed on 14 cadaveric specimens to assess the number of PIA perforators at the distal third of the forearm, along with the distance of the perforators from the ulnar styloid. Additionally, the pedicle distance from the pivot point to the lateral epicondyle was recorded. A clinical study in 4 patients with elbow soft-tissue defects treated with the antegrade PIA was also performed to assess viability and clinical outcomes. Results: A mean of 3 perforators (range, 2–4) of the PIA were found in the distal third of the forearm. The pedicle distance from the pivot point to the lateral epicondyle was 10 cm (range, 8–11.5 cm). In the clinical study, all cases treated with the antegrade PIA flap showed satisfactory outcomes without loss of the flap or significant partial necrosis. Conclusion: In this limited series, the antegrade PIA flap has shown to be a reliable and effective alternative for treatment of soft-tissue defects at the elbow. The PIA perforators in the distal forearm and the pedicle length allow the flap to easily reach the elbow.